Civil society, freedom of the press, and democracy in Iraq since 2003 - Nasir, Farsat Mamil (KDI School, 2012)
In 2003 Iraq found a basic change in its ruling system with the collapse of the previous regime, but this change did not become a factor for political, social, and economic development in the country. The Iraqi government did not succeed in strengthening the principles of democracy to guarantee and secure the rights of citizens. Despite this, the media outlets and civil society organizations came in to the country and their number increased, but they could not contribute in the development process of democracy because they faced restrictions and difficulties. The freedom of expression and the press which are strong factors of democracy have remained undermined and restricted. The journalists in Iraq face killing and intimidation and their lives are not secure. The rule of law which is significant to maintain justice and equality is very weak or absent because of political parties interference in the courts and a biased judicial system. Therefore, the journalists who accompany civil society organizations are not able to check and monitor the government’s policy and reveal corruption by officials. As a result, the continuation of political instability and conflict between Iraqi political parties which is the main reason for the weakness of the rule of law has had a negative effect on the condition of the freedom of press, civil society and the growth of democracy.
Thesis(Master) --KDI School:Master of Public Policy,2012